The effect of pulp and cellulose nanofiber cyanoethylation on the physical properties of transformer insulating paper - Mohammad Azadfallah (Regional Information Center for Science and Technology (RICeST), 2016)
The properties of transformer electrical insulating papers are influenced by fiber chemical modification process. In this research, the effect of cyanoethylation of fibers and addition of cyanoethylated cellulose nanofiber (CNF) on dielectric properties including capacitance, dielectric loss, insulation resistance, breakdown voltage as well as tensile strength of two grade of handsheets made of unbleached long fibers and its mixture with bagasse soda pulp (with the ratio of 1:1) were evaluated after impregnating with mineral oil. Cyanoethylation of CNF and pulp fibers was performed by grafting of acrylonitrile under alkaline condition at 40 ̊C and room temperature respectively. Then, the nitrogen content of cyanoethylated samples was determined using Kjeldahl method and degree of substitution (DS) was calculated. The results showed that cyanoethylation of pulp fibers and CNF decreased the capacitance and tensile strength of insulated papers. It was also observed that the chemical modification imposed slight effect on dielectric loss, but insulation resistance and dielectric voltage were increased.